The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/aoa-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Loudness Scaling Test Based on Categorical Perception

Abstract: The main goal of this research study is focused on creating a method for loudness scaling based on categorical perception. Its main features, such as: way of testing, calibration procedure for securing reliable results, employing natural test stimuli, etc., are described in the paper and assessed against a procedure that uses 1/2-octave bands of noise (LGOB) for the loudness growth estimation. The Mann-Whitney U-test is employed to check whether the proposed method is statistically equivalent to LGOB. It is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The aim of the recordings was to collect the real research material reflecting the auditory sensations which a person on a sidewalk in an immediate vicinity of a busy road was exposed to. The material was supposed to be used in the future for the subjective assessment of the nuisance of traffic noise using the method of loudness scaling [15,30]. During the recordings and measurements, the microphone was placed on the stand at a height of 170 cm, which is a head height of a potential adult passer-by, and halfway up the width of the sidewalk, i.e.…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…The aim of the recordings was to collect the real research material reflecting the auditory sensations which a person on a sidewalk in an immediate vicinity of a busy road was exposed to. The material was supposed to be used in the future for the subjective assessment of the nuisance of traffic noise using the method of loudness scaling [15,30]. During the recordings and measurements, the microphone was placed on the stand at a height of 170 cm, which is a head height of a potential adult passer-by, and halfway up the width of the sidewalk, i.e.…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…Before starting the main test, each person underwent a training phase to adjust the volume and become familiar with the listening equipment. Further information on loudness and related topics may be found in (Kostek et al, 2016;Maijala et al, 2018;Une, Miyazaki, 2020).…”
Section: Qoe Evaluationmentioning
confidence: 99%
“…4, but that this has rarely been done outside of Hellman's own work. A number of studies have shown recruitment functions with level on the abscissa and CUs on the ordinate (e.g., Garnier et al, 2000;Brand and Hohmann, 2002;Rasetshwane et al, 2015;Kostek et al, 2016;Oetting et al, 2016), but those functions are all distorted by the transform between CUs and loudness. Use of CU sone values provides functions closer in form to those shown by Hellman andMeiselman (1990, 1993).…”
Section: B Advantages Of the Cu Sone Transformmentioning
confidence: 99%